Thyroid Hydatid Cyst.: One Case - Parma, Dante; Belloso, Rogelio; Iraola, María L; Galaret, María; Cuevas, Luisa (Cirugía del Uruguay, 1980)
A new case of Thyroid :Ej:ydatid Cyst -the 11th. in our country- is reported. This patho!ogy is rare, according to clinical and laboratory data, in its systematic clinical symptomatology. The paper contains a brief review of the 11 cases already published.